Variability Management in Dynamic Software Product Lines: A Systematic Mapping - Guedes, Gabriela; Silva, Carla; Soares, Monique; Castro, Jaelson (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2015: Anais do IX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2015)
Dynamic Software Product Lines (DSPLs) are SPLs in which the product configuration may occur at runtime. Over the last decade, DSPL has gained the interest of researchers as a way of modelling and developing dynamically adaptive systems. We have conducted a systematic mapping to discover how variability is modelled in DSPL approaches and which information is used to guide variability binding at runtime. This paper presents the results of our systematic mapping, which can be used to identify research trends and gaps for variability management in DSPLs.